Polyethersulfone/polyvinyl acetate blend membrane incorporated with TiO2 nanoparticles for CO2/CH4 gas separation (Malaysian Journal of Fundamental and Applied Sciences, 2017)
Development of polymer blend membranes is gaining much attention especially for gas separation processes. This paper is primarily focused on synthesizing polymer blend membranes incorporated with titanium dioxide (TiO2) nanoparticles as inorganic filler to enhance its performances. Polyethersulfone (PES) and polyvinyl acetate (PVAc) were blended at ratio of 90/10, together with 5 wt.% of TiO2 in dimethylformamide (DMF). The morphological structure of the membrane was analysed via FESEM. It shows that a rigid/non-porous membrane with slight nanoparticles agglomeration was formed. As interpreted from TGA, incorporating TiO2 nanoparticles into the polymer blend reduces the degradation temperature, increases wt.% of leftover residual thus proves an enhancement in thermal stability of the membrane. Moreover, the presence of TiO2 nanoparticles in the developed membrane possesses some effect on the spectral analysis as observed via FTIR spectroscopy. The permeability of CO2 gas is improved with addition of TiO2 nanoparticles within the blend membrane and better selectivity of CO2/CH4 is observed.
Keywords: Polymer blend membrane; PES/PVAc; TiO2 nanoparticles; inorganic filler; gas separation